Uncalibrated Hydrographic Data acquired with a CTD in the Ross Sea during the Nathaniel B. Palmer expedition NBP0601 (2005) (IEDA: Marine-Geo Digital Library, 2006)
This data set was acquired with a Sea-Bird SBE-911 CTD during Nathaniel B. Palmer expedition NBP0601 conducted in 2005 (Chief Scientist: Dr. Giacomo DiTullio). These data files are of SEASOFT format and include Conductivity, Temperature, and Pressure data that have not been processed. Data were acquired as part of the project(s): Interaction of iron, light and CO2 on phytoplankton community dynamics in the Ross Sea, and funding was provided by NSF grant(s): ANT03-38097, ANT03-38157, ANT03-38164, and ANT03-38350. This data was cited by Smith et al., 2013.